Family and Nurse Prognostication in Chronic Critical Illness - J. Daly, Barbara; L. Douglas, Sara; R. Lipson, Amy (International Journal of Nursing Research, 2023)
Aims: The aim of this study was to describe similarities and differences over time in expectations held by family members of long-term critically ill patients and the nurses caring for those patients. Materials: In addition to demographic data, outcome expectations of family decision makers and ICU nurses were obtained by asking each participant to indicate expectations for the patient, 6 months in the future, for survival, cognition, and functional status. Families also were asked what kind of information was most important in understanding the patient’s condition and what was most important in making decisions. Methods: This was a descriptive correlational analysis. Nurses and family members were surveyed on the 3rd–5th day of the patient’s stay, and every 5 days until discharge or death. Correlations between nurse and family predictions were examined using Pearson R. Repeated measures analysis of variance (RMANOVA) was used to explore the relationship between the family member’s rating of what was most important in the care of the patient (survival vs. quality of life) and that individual’s prediction of the likelihood of survival, over time. Results: Family members consistently predicted better outcomes than nurses, with >80% of families predicting a high likelihood of survival, while <50% of nurses thought survival probability was high. There were similar differences in expectations for functional status and cognition. Between 14% and 23% of families indicated it was talking with the nurses that were most important. Conclusions: Results suggest a need for design and tests of nurse interventions aimed at improving family understanding of patient prognosis and future outcomes.